Local Champions Berkarakter Kewirausahaan Sosial dan Strategi Penyuluhan untuk Pengembangan Pusat Pelatihan Pertanian dan Pedesaaan Swadaya - Defitriani, Defitriani; Madarisa, Fuad; Silfia, Silfia; Tanjung, Hery Bachrizal (Syntax Literate, 2025)
This study aims to describe the characteristics of local champions based on social entrepreneurship as well as effective extension strategies in the development of Independent Agriculture and Rural Training Centers (P4S). Local champions are defined as individuals or groups who play an important role in leading and driving positive change in communities, especially in agricultural and rural contexts. This research uses qualitative and quantitative methods with a case study approach, which was carried out at P4S Permata Ibu as a pilot and P4S Agrotourism Arizafarm as a target. The results of the study show that local champions with the spirit of social entrepreneurship have a crucial role in growing and developing P4S. Characteristics such as strong leadership, social commitment, ability to innovate, networking skills, and managerial skills are key to their success. With the right support from stakeholders, they can be significant agents of change in improving the well-being of farmers and rural communities. The spirit of social entrepreneurship owned by local champions includes values such as honesty, active community involvement, fair profits, and concern for the environment. In addition, effective extension strategies include a participatory approach, the application of information technology, and close collaboration with various parties, including governments, universities, the private sector, and non-governmental organizations. The conclusion of this study is that the sustainable development of P4S requires support from local champions with the spirit of social entrepreneurship and the implementation of effective counseling strategies.